BLENDED LEARNING IN FRENCH INTERMEDIATE GRAMMAR LEARNING: IS IT EFFECTIVE? - Roswita Lumban Tobing; Dwiyanto Djoko Pranowo (Jurnal Cakrawala Pendidikan, 2020)
The use of blended learning in foreign language instruction such as French has been widely practiced by teachers in many countries, including Indonesia. As French for Indonesian is somehow not an easy subject to learn, the blended learning has not been widely implemented. In this regard, the aim of this study was to investigate whether there could be an improvement in the quality of learning when blended learning in French Intermediate Grammar courses for Indonesian was applied. An embedded mixed method design consisting of quantitative and qualitative approaches was used to analyse the collected data in this research, where the main method was quasi-experiment using the pretest-posttest design.  This study was conducted in one semester in seven synchronization activities. Data were collected by tests, questionnaires and observation sheets from 37 students taking French intermediate grammar course as the research respondents. The tests were reliable (Alpha Cronbach = .925). Moreover, the results showed that there were significant improvements among students, thus suggesting that blended learning can maximize the quality of learning (sig. .05). The qualitative data informs that students were more independent in developing their creativity, autonomy and innovation in managing blended learning, hence the learning outcome was achieved.